Socio-demographic and Clinical Characteristics of Patients with Ulcerative Colitis at a Tertiary Care Centre in Nepal
Introduction: The prevalence of ulcerative colitis (UC) has gradually increased in Asia over the last few decades. However, there is a paucity of data regarding UC in Nepal. This study analyzed the socio-demographic and clinical characteristics of patients hospitalized with UC. Methods: This is a hospital based, cross-sectional study. Data was collected among 100 individuals admitted to the hospital with UC from June 2016 to May 2018. A descriptive analysis of the demographic and clinical characteristics was done. Results: Of the 100 patients 51 were male (M:F ratio 1.04:1). Average age at diagnosis was 38